Meningkatkan Kosa Kata Bahasa Inggris Peserta Didik Kelas 3 Sekolah Dasar Melalui Lagu - Nasrullah, Nasrullah; Putri, Nur Indah Dwi; Fitriasih, Nunung (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve English vocabulary mastery of grade 3 elementary school students through song learning methods. This study was conducted in two cycles, where each cycle consists of planning, action implementation, observation, and reflection stages. The subjects of the study were 29 grade 3 students. Data were collected through vocabulary tests and observations of student activities during the learning process. The results showed an increase in students' vocabulary skills. In the first cycle, 62.07% of students achieved the Minimum Completion Criteria (KKM), while in the second cycle the number of students who achieved KKM increased to 86.21%. The use of songs in learning has proven effective in increasing student motivation and learning outcomes.